Hyperbolic normal almost contactmetric hypersurfaces in Euclidean 4-dimensional space - Baškienė, Angelė (Lietuvos matematikos rinkinys, 2005)
In Euclidean 4-dimensional space, all hyper surfaces with normal almost contact metric structure of hyperbolic type as well as hyperbolic Sasakian structure are found.